Organic Acids Modulate Systemic Metabolic Perturbation Caused by Salmonella Pullorum Challenge in Early-Stage Broilers - Wang, Jing; Dai, Dong; Zhang, Hai-jun; Wu, Shu-geng; Han, Yan-ming; Wu, Yuan-yuan; Qi, Guang-hai (Frontiers in Physiology, 2019)
The objectives of this study were to determine the protective effects of organic acids in broilers exposed to Salmonella Pullorum challenge at early stage, and to explore the potential benefits of organic acids by metabolomics analysis. The treatment groups included non-challenged, S. Pullorum-challenged, challenged group supplemented with virginiamycin, challenged group supplemented with organic acids in drinking water, challenged group supplemented with organic acids in feed, and challenged group supplemented with organic acids in combination in drinking water and feed. Results showed that early Salmonella challenge induced an acute systemic infection of broilers in the starter phase, followed by the grower phase without triggering clinical signs. Organic acids supplementation promoted growth during the grower phase, and while organic acids in water contributed more, the positive effects of organic acids in combination were comparable to those of virginiamycin supplementation in challenged birds. Furthermore, organic acids could modulate the systemic metabolic perturbation caused by challenge as it alleviated stress responses mediated by steroid hormone, potentially attenuated antioxidant or immune defense, and modified intestinal microbiota metabolism. These results show a metabolic mechanism that may partly explain the potential benefits of organic acids in Salmonella challenged birds, and may contribute to the use of organic acids to control or reduce S. Pullorum infection in farm animals.